Step-by-step explanation:
[tex]a^{-n}=\dfrac{1}{a^n}\\\\\text{Therefore your answer:}\\\\3^{-1}=\dfrac{1}{3}<\dfrac{1}{2}\\\\4^{-1}=\dfrac{1}{4}<\dfrac{1}{2}\\\\5^{-1}=\dfrac{1}{5}<\dfrac{1}{2}\\\vdots\\2^{-2}=\dfrac{1}{2^2}=\dfrac{1}{4}<\dfrac{1}{2},\ (-2)^{-2}=\dfrac{1}{(-2)^2}=\dfrac{1}{4}<\dfrac{1}{2}\\\\\\3^{-2}=\dfrac{1}{3^2}=\dfrac{1}{9}<\dfrac{1}{2},\ (-3)^{-2}=\dfrac{1}{(-3)^2}=\dfrac{1}{9}<\dfrac{1}{2}\\\\4^{-2}=\dfrac{1}{4^2}=\dfrac{1}{16}<\dfrac{1}{2},\ (-4)^{-2}=\dfrac{1}{(-4)^2}=\dfrac{1}{16}<\dfrac{1}{2}\\\vdots\\2^{-3}=\dfrac{1}{2^3}=\dfrac{1}{8}<\dfrac{1}{2}\\\vdots[/tex]